Implementasi Perbup Jombang Nomor 41 Tahun 2019 Terhadap Pembentukan Karakter Spiritualitas Siswa (Studi Kasus di SDN Jombang 2) - Nur Qurnia; Fatkhulloh Abdul Malik; Didin Sirojudin (Universitas KH. A. Wahab Hasbullah, 2022)
This thesis discusses the implementation of the Jombang Regent Regulation Number 41 of 2019 on the formation of the spiritual character of students located at SDN Jombang 2. The background is the application of this regulation which is applied in public schools, while the curriculum in it contains the curriculum of Islamic boarding schools. This study aims to determine the effectiveness and factors that influence the implementation of these regulations. This type of research is descriptive qualitative where the researcher conducts observations, interviews and documentation in order to obtain the data needed for research. The application of these regulations is considered effective in increasing the spirituality of the students of SDN Jombang 2 although there are several influencing factors, both internal and external.